ANALYSIS OF SERVICE USAGE DECISIONS AND BRAND IMAGE ENHANCEMENT AT COURTESY AGENTS IN BATAM CITY - Yulianto Putra, Edy; Juwita Depari, Irene; Nainggolan, Ferdinand (Distribusi - Journal of Management and Business, 2024)
Marketing strategies have to evolve to increase service usage decisions and the company's brand image. In previous studies, it was stated that digital marketing, price, and trust were proven to influence service usage decisions and brand image. This study also aims to examine the effect of digital marketing, price, and trust on service usage decisions and brand image at Courtesy Agents, so that Courtesy Agents management can develop the right strategy to increase customers and brand image. By using quantitative methods and SmartPLS to analyze data obtained through questionnaires with respondents who are customers of Courtesy Agents services in making work permits for foreign workers, this study obtained the results that it is true and proven that digital marketing, price, and trust have a positive and significant effect on service usage decisions and brand image at Courtesy Agents, except for the price variable which has no significant effect on brand image.